Alternate complement pathway activation by group A streptococci: role of M-protein. - Bisno, A L (1979)
Avirulent strains of group A streptococci readily activate the complement system in normal human serum via the alternate complement pathway (ACP). Virulent M-positive group A streptococci are much less potent as activators of the ACP. The ability of M-positive streptococci to activate the ACP is enhanced by trypsinization or mild peptic digestion. The latter treatment removes the serologically active and antiphagocytic type-specific moieties of M protein, but retains the surface fuzzy layer. The phagocytosis of avirulent streptococci is markedly enhanced by preopsonization in serum chelated with Mg-ethylene glycol tetraacetic acid (classic complement pathway blocked) but not in serum devoid of heat-labile factors. These studies suggest that the function of M protein as a virulence factor may be mediated, at least in part, by its ability to retard interaction of ACP components with structures present on the streptococcal cell surface.